2012
DOI: 10.1111/his.12011
|View full text |Cite
|
Sign up to set email alerts
|

The value of immunophenotyping hepatocellular adenomas: consecutive resections at one UK centre

Abstract: The distribution of adenoma types in this population matches that in others, and immunoprofiling is required for accurate typing. Carcinoma ex-adenoma is uncommon and fits the published risk profile (large size and GS-positive).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 34 publications
2
13
1
Order By: Relevance
“…However, occasional hepatic adenomas and focal nodular hyperplasias can have a diffuse pattern that is essentially indistinguishable from hepatocellular carcinoma [ 29 -32 ]. For example, one study found diffuse sinusoidal CD34 staining in 27 % of hepatocellular adenomas, which correlated with beta catenin activated or unclassifi ed type of adenomas [ 32 ]. For all of these reasons, CD34 is used less often than some of the other available stains and is never used alone, but can still be useful.…”
Section: Cd34 Stainmentioning
confidence: 99%
“…However, occasional hepatic adenomas and focal nodular hyperplasias can have a diffuse pattern that is essentially indistinguishable from hepatocellular carcinoma [ 29 -32 ]. For example, one study found diffuse sinusoidal CD34 staining in 27 % of hepatocellular adenomas, which correlated with beta catenin activated or unclassifi ed type of adenomas [ 32 ]. For all of these reasons, CD34 is used less often than some of the other available stains and is never used alone, but can still be useful.…”
Section: Cd34 Stainmentioning
confidence: 99%
“…These histologic and immune-phenotypic features upon which the diagnosis of HCC was made have been wellestablished. [25][26][27] The diagnosis of HCC in this H-HCA was independently rendered by three liver pathologists from three different institutions. Although H-HCA has been considered to be without malignant potential, the relative rarity of HCAs, as well as their relatively early detection, may account for this impression.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings of inconsistent GS staining results are discussed in a review of HCA cases from Scotland. 27 In addition to these difficulties with immunohistochemistry, β-HCA can be difficult or impossible to be distinguished from well differentiated HCC because of the cytological atypia and acinar growth pattern. 8 …”
Section: Discussionmentioning
confidence: 99%